Kitab Undang-Undang Tambo Kerinci (TK) 215 - Kozok, Uli (Jumantara: Jurnal Manuskrip Nusantara, 2023)
When the Dutch linguist Dr. Petrus Voorhoeve was commisioned in 1942 to document and transliterate manuscripts that were kept as heirlooms by the people of Kerinci, Sumatra, he encountered more than 250 manuscripts, most in Malay language, and in three different scripts: Old Sumatran, Kerinci Incung script, and Jawi (Arab-Malay). The manuscripts were recorded and transliterated in a book entitled Tambo Kerinci (TK).  TK 214 is a manuscript on tree bark in Old Sumatran scipt entitled Nitisarasamuccaya. This code of law was composed in the 14th century in Dharmasraya, West Sumatra. Written possibly during Adityawarman’s reign. In the Tanjung Tanah heirloom collection is a second code of law, TK 215, written in Arab-Malay script on paper, is essentially an 18th century re-interpretation of TK 214.